Foreword—Evolving Business Associations: Understanding the Role of Law - Robert B. Thompson (Washington University Law Quarterly, 1992)
This Symposium presents an array of provocative articles and commentary addressing law as applied to close corporations and going-private enterprises. These articles define anew how we think about the business firm and also offer guidance for defining the role of law and private ordering for all business enterprises.